Correlation between immunoglobulin index level and disease severity and clinical manifestations in children with atopic dermatitis as a chronic inflammatory: Immunoglobulin index level and atopic dermatitis - Zheng, Xin; Chen, Shuibao; Chen, Lang; Ye, Zhenjie (Cellular and Molecular Biology, 2023)
It was to analyze the clinical characteristics of atopic dermatitis (AD) in children and its relationship with immunoglobulin (IgG, IgA, IgM, IgE) levels. 400 children with AD in the dermatology clinic of Shengli Clinical Medical College of Fujian Medical University, Fujian Provincial Hospital(SCMC-FMU) were the study subjects, and 200 normal children were enrolled as the blank control. The clinical data of the included children were collected, and the serum immunoglobulin levels and other related indicators were measured. The results showed that the IgE level was higher observably in group A when we compared it with group A0, the IgE level was much higher in group B in comparison to group B0, group C showed higher IgE level C than in group C0, and it was the same case in groups D and D0(P < 0.05). The IgM level was decreased greatly in group C than that in normal children in group C0 (P < 0.05), but showed no visible difference among other groups (P > 0.05). The O-SCORAD scores of groups A, B, C, and D were significantly positively correlated with IgE level (P < 0.05). No great correlation was observed between skin dryness and IgE-specific allergen, IgG, IgA, IgM, and IgE levels in groups A - D (P > 0.05). Immunoglobulin deficiency was present in AD children compared with normal children, and IgE could be used as an efficient indicator to assess the severity of AD in children.